A review of the Oocyclus Sharp of Venezuela with description of twelve new species (Coleoptera: Hydrophilidae: Laccobiini) - Short, Andrew E. Z.; García, Mauricio (Zootaxa, 2010)
The water scavenger beetle genus Oocyclus Sharp is reported from Venezuela for the first time. A review of more than 3000 specimens revealed fourteen species, including twelve described as new: O. andinus sp. n., O. bolivari sp. n., O. coromoto sp. n., O. floccus sp. n., O. galbus sp. n., O. meridensis sp. n., O. petra sp. n., O. pico, sp. n., O. pittieri sp. n., O. sapphirus sp. n., O. trujillo sp. n., and O. zulianus sp. n. Two species previously known only from Central America, O. maculatus Sharp and O. substillus Short & Perkins, are recorded for the first time in South America from localities along the Andean border with Colombia. Nearly all species are associated with hygropetric habitats such as wet rocks, waterfalls, and seepages; one species, O. petra, was also occasionally found in sandy stream margins that lacked rock substrate. The Neotropical genus Beralitra d’Orchymont is placed in synonymy with Oocyclus, yielding two newcombinations: Oocyclus obscurus (d’Orchymont) comb. n. and Oocyclus iguazu (Oliva) comb. n. A key to the Venezuelan species of Oocyclus is provided in addition to habitus and diagnostic character illustrations.